2004
DOI: 10.1007/s00246-003-0450-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Cardiac Output Measured by the Pulmonary Arterial Thermodilution Technique and that Measured by the Femoral Arterial Thermodilution Technique in a Pediatric Animal Model

Abstract: This study compares the correlation between two methods for the determination of cardiac output-the pulmonary arterial thermodilution technique using the Swan-Ganz catheter and the femoral arterial thermodilution technique using a pulse contour analysis computer (PiCCO) catheter. We performed a prospective animal study using 16 immature Maryland pigs weighing 9 to 16 kg. A 5.5- or 7.5-Fr Swan-Ganz catheter was introduced into the femoral or jugular vein, and a 4- or 5-Fr arterial PiCCO catheter was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
5
24
0
3
Order By: Relevance
“…Other less invasive methods like PiCCO could be useful to measure cardiac output and at the same time to estimate the circulating volume. [17][18][19] In this sense, the correlation found between CI and ITBI could suggest the CI dependence of an adequate volume status during asphyxia, CPR and ROSC. However, and due to the fact that PiCCO system measures ITBI and CI by the same thermodilution method, some link between both measurement cannot be discarded.…”
Section: Correlation Between Global Hemodynamic Parametersmentioning
confidence: 94%
“…Other less invasive methods like PiCCO could be useful to measure cardiac output and at the same time to estimate the circulating volume. [17][18][19] In this sense, the correlation found between CI and ITBI could suggest the CI dependence of an adequate volume status during asphyxia, CPR and ROSC. However, and due to the fact that PiCCO system measures ITBI and CI by the same thermodilution method, some link between both measurement cannot be discarded.…”
Section: Correlation Between Global Hemodynamic Parametersmentioning
confidence: 94%
“…Femoral arterial thermodilution measurement has been used in infantile animal models and in children [17][18][19][20][21][22][23][24]; it has showed an acceptable correlation with pulmonary arterial thermodilution by using a Swan-Ganz catheter [19,23], and therefore it might be a reliable and less invasive hemodynamic monitoring tool in the post-CA period in children.…”
Section: Cardiovascular Parametersmentioning
confidence: 99%
“…This technique may be used in children of any age, including neonates (3,4). A number of studies have shown that a good correlation exists between the output measured by pulmonary artery and femoral artery thermodilution (3)(4)(5).…”
mentioning
confidence: 99%